Spectroscopic analysis of petroleum products and lubricants - Nadkarni, R. A. (ASTM International, 2011)
"This unique publication examines twelve spectroscopic techniques used in oil industry laboratories.
"ASTM stock number: MONO 9."
Keywords: Petroleum products -- Analysis.; Lubricating oils -- Analysis.; Spectrum analysis.; Petroleum -- Spectra.; elektronické knihy; electronic books